COMPETITIVE ADVANTAGES OF BULGARIAN SUNFLOWER INDUSTRY AFTER THE ACCESSION INTO THE EUROPEAN UNION - Krum HRISTOV; Rositsa BELUHOVA-UZUNOVA; Mariyana SHISHKOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
After the accession to the EU the oilseed crops, especially sunflower and rapeseeds, are becoming promising and advanced sector in Bulgarian agriculture. They account for more than 20% of total agricultural output and dominate in structure of Bulgarian export. Bulgaria and Romania are the largest sunflower seed producers in the EU, with sunflower yields increasing twice over the past ten years. The results in the sector are good starting point for a debate over its competitiveness and efficiency. The aim of the study is to analyze the competitive advantages of Bulgarian sunflower industry and to outline opportunities and challenges for post 2020 period. The sector is observed in terms of production, consumption and trade. Several of the commonly used indicators for the evaluation of competitive advantages have been applied such as the Relative index of export advantages – RXA, the Relative trade advantage – RTA and Related competitiveness – RC. The results show that sunflower seed will continue to dominate in Bulgarian agricultural structure regardless the dynamic of international prices and production. The difficulties in Bulgarian livestock are reflecting the sector and causing dependence on export and foreign trade.